Supraclavicular Approach to Ultrasound-Guided Brachiocephalic Vein Cannulation in Children and Neonates - Zied Merchaoui; Ulrik Lausten-Thomsen; Ulrik Lausten-Thomsen; Florence Pierre; Maher Ben Laiba; Nolwenn Le Saché; Pierre Tissieres; Pierre Tissieres (Frontiers Media S.A., 2017)
The correct choice of intra vascular access in critically ill neonates should be individualized depending on the type and duration of therapy, gestational and chronological age, weight and/or size, diagnosis, clinical status, and venous system patency. Accordingly, there is an ongoing demand for optimization of catheterization. Recently, the use of ultrasound (US)-guided cannulation of the subclavian vein (SCV) has been described in children and neonates. This article gives an overview of the current use of US for achieving central venous catheter placement in the SCV or the brachiocephalic vein (BCV) in neonates. More than 1,250 catheters have been reported inserted in children and neonates for a cumulated success rate of 98.4% and the complication rate is reported to be low. The technical aspects of various approaches are discussed, and we offer our recommendation of an US-guided technique for SCV and BCV cannulation based on our experience in a large NICU setting. Although the cannulation the SCV or BCV does not substitute the use of peripherally inserted central catheters or umbilical venous central catheters in neonates, it is a feasible route in very small children who are in need of a large caliber central venous access.